2003
DOI: 10.1067/mva.2003.231
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral hyperperfusion syndrome after carotid endarterectomy: Predictive factors and hemodynamic changes

Abstract: These data do not corroborate the common belief that CHS occurs preferentially in patients with severe ipsilateral or contralateral carotid disease, increased intraoperative cerebral perfusion, or severe hypertension. Recently performed contralateral CEA (<3 months) appears to be predictive of CHS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
47
1
5

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 101 publications
(55 citation statements)
references
References 26 publications
(37 reference statements)
2
47
1
5
Order By: Relevance
“…However, the ICA is much larger than other intracranial arteries like the middle cerebral artery and can readily bring about hyperperfusion syndrome after the stenotic lumen is resolved by stenting. Hyperperfusion is thought to occur more frequently after carotid endarterectomy and carotid stenting (14,15); however, in our study, seven patients (12.1%) had headache and dysphoria after stenting, which was probably related to post-stenting hyperperfusion despite normal cranial CT findings. Atherosclerotic stenosis in intracranial ICA is prone to high recurrent stroke rate in spite of intensive medication, and the WASID study revealed that patients with intracranial ICA stenosis had an endpoint event rate of 20% either with aspirin or warfarin treatment over a 1.8-year follow-up period (8).…”
Section: Discussioncontrasting
confidence: 48%
“…However, the ICA is much larger than other intracranial arteries like the middle cerebral artery and can readily bring about hyperperfusion syndrome after the stenotic lumen is resolved by stenting. Hyperperfusion is thought to occur more frequently after carotid endarterectomy and carotid stenting (14,15); however, in our study, seven patients (12.1%) had headache and dysphoria after stenting, which was probably related to post-stenting hyperperfusion despite normal cranial CT findings. Atherosclerotic stenosis in intracranial ICA is prone to high recurrent stroke rate in spite of intensive medication, and the WASID study revealed that patients with intracranial ICA stenosis had an endpoint event rate of 20% either with aspirin or warfarin treatment over a 1.8-year follow-up period (8).…”
Section: Discussioncontrasting
confidence: 48%
“…[24][25][26][27][28][29][30][31][32] The mechanism remains unclear, but preoperative impairment of autoregulation due to chronic hypoperfusion resulting from contralateral ICA occlusion is one of the risk factors. [32][33][34] To prevent this syndrome, strict control of blood pressure during the postoperative period has been emphasized in many reports. [22][23][24]33 Hyperperfusion did not occur in any of our patients; however, the possible occurrence of this condition should be recognized.…”
Section: Discussionmentioning
confidence: 99%
“…[5][6][7] Risk factors for hyperperfusion have been proposed, including high-grade stenosis, poor collateral circulation, high blood pressure, age, and bloodbrain barrier breakdown. [7][8][9][10][11] Nevertheless, the underlying pathophysiology of HPS has not been well evaluated due to its low incidence (0.7%-3%). 7,9,12 The generally accepted explanation emphasizes a failure of autoregulation after sudden augmentation of cerebral blood inflow following carotid stent placement.…”
mentioning
confidence: 99%